PENGARUH PENAMBAHAN TEPUNG DAUN KELOR (Moringa Oleifera L.) TERHADAP KARAKTERISTIK FISIK, KIMIA DAN SENSORI SIOMAY IKAN NILA (Oreochromis niloticus) - Arni, Siti Murdila; Koesoemawardani, Dyah; Indraningtyas, Lathifa; Zuidar, Ahmad Sapta (Jurusan Teknologi Hasil Pertanian, 2024)
Processed fishery products in the form of dumpling are high in carbohydrates and protein, because they are made from at least 30% minced meat mixed with flour and other ingredients. However, dumpling is low in fiber and needs to be supplemented with high fiber ingredients, such as Moringa leaf flour. The aim of this research is to determine the effect of adding Moringa leaf flour on the physical, chemical and sensory characteristics of tilapia dumpling, as well as to establish the proportion of Moringa leaf flour addition that produces the best tilapia dumpling in accordance with SNI 7756:2013. The research was conducted using a Complete Randomized Block Design (RAKL) with one factor and four replications consisting of 6 levels, namely the concentration of Moringa leaf flour addition of 0% (P1), 1% (P2), 2% (P3), 3% (P4), 4% (P5) and 5% (P6). The best treatment is determined using the star method. The research findings indicated that the addition of Moringa leaf flour had influenced the physical, chemical, and sensory characteristics of tilapia fish dumpling. The best treatment for tilapia dumpling was treatment P6 (5%) with a gel strength value of 122.37g, water content of 58.97%, texture of 3.24 (chewy), taste of 4.54 (very characteristic of Moringa), aroma of 4.75 ( very characteristic of Moringa) color of 4.87 (dark green), ash content of 2.24%, crude fiber content of 12.53%, fat content of 1.97%, protein content of 12.19% and antioxidant activity of 4087.90 ppm.